HSSCIoT: An Optimal Framework Based on Internet of Things-Cloud Computing for Healthcare Services Selection in Smart Hospitals - Oanh Nguyen (Advances in Engineering and Intelligence Systems)
The combination of the Internet of Things (IoT) and cloud computing has been used in many fields, making global customized interest. Recently, this technology has been considered in the medical and healthcare industries. Understanding the challenges and opportunities of using IoT-cloud in modern healthcare systems needs more knowledge and strategies. This trend can be implemented in smart hospitals with Hospital Information Systems (HIS) to provide a successful structure for better management in a new era (especially in the coronavirus pandemic). Proposing a new schema for HIS based on IoT-cloud as an assumption and formulating some advanced models for the three components of notification, database, and data processing provided in the DEMATEL protocol. In general, this article proposes a new framework of Healthcare Services Selection-based Internet of Things-Cloud (HSSCIoT) in HIS for smart hospitals that use deep learning techniques to process any data. The combination of Recurrent Neural Networks (RNN) means Long Term Short Memory (LSTM) and new kinds of Convolutional Neural Networks (CNN) means Atrous Spatial Pyramid Pooling (ASPP) deep learning methods considered for HSSCIoT.